Best Sourcing - Towards Lean ICT Shared Services In A Singapore Government Organisation - Loh, Kah Heng, Daniel (2008)
Many government organisations in Singapore have been embarking on a strategic decision to drive lean public service by pushing down costs for operating expenditures, improving service performance and concentrating all or most of the resources available on core business. In such circumstances, outsourcing becomes almost inevitable. Outsourcing allows the organisation to focus on its core business by transferring operational functions to external specialists.